A REQUIREMENT ENGINEERING IN REPORTING AND COUNSELING-BASED ASSISTANCE APPLICATION FOR VICTIMS OF VIOLENCE AGAINST WOMEN - Dwi Hosanna Bangkalang; Nina Setiyawati; Radius Tanone; Hanna P. Chernovita; Yuliana T. B. Tacoh (Jurnal Riset Informatika, 2021)
Requirements engineering is the initial phase of the software development life cycle it is a critical aspect of application development since it has a significant impact on the results of the product being created. This article focuses on the engineering requirements of the web-based application development process for reporting and assisting victims of violence against women using the Loucopoulos and Kanakostas Iterative Requirements Engineering Process Model. The application was created to contribute to the solution of the problem of violence against women in Indonesia, where violence against women is an iceberg phenomenon because not all incidents are reported. Furthermore, victims of violence against women require support in receiving emotional support in the form of counseling, which can be done online via chat or video calls. The results of these requirements engineering are alternative solutions, application feature design, database design, system modeling using UML, and application architecture design. The validation of requirements engineering was carried out using a low fidelity prototype